1999
DOI: 10.1038/sj.leu.2401510
|View full text |Cite
|
Sign up to set email alerts
|

False human hematopoietic cell lines: cross-contaminations and misinterpretations

Abstract: nized in the scientific community. Even if the contaminating cells have only a slight growth advantage, the intruding cells will overgrow and completely replace the original cell line, sooner or later. The most notorious culprit of such cross-contamination is, of course, the infamous solid tumor cell line HeLa. 3 The history of cell cross-contamination in cell cultures is long and painful; the first report on cell line cross-contamination appeared in 1957. [4][5][6][7][8][9] The advent of forensic DNA profilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(53 citation statements)
references
References 9 publications
3
50
0
Order By: Relevance
“…47 Of the remainder, AG-F and CO are cross-contaminated in both cases by the T cell ALL cell line, CCRF-CEM. 82 Hence, the characterization of the shortlisted HDLM-1/2/3, KM-H2, L-428 and L-540 assumes added importance. By portraying the cytogenetic picture of HD, the claim of HDLM cells to act as in vitro models is strengthened.…”
Section: A Model and A Resourcementioning
confidence: 99%
“…47 Of the remainder, AG-F and CO are cross-contaminated in both cases by the T cell ALL cell line, CCRF-CEM. 82 Hence, the characterization of the shortlisted HDLM-1/2/3, KM-H2, L-428 and L-540 assumes added importance. By portraying the cytogenetic picture of HD, the claim of HDLM cells to act as in vitro models is strengthened.…”
Section: A Model and A Resourcementioning
confidence: 99%
“…1,4 Details of the various methods employed for the identity and quality control and characterization of MUTZ-5 cells have been described elsewhere: DNA fingerprinting, 5 immunophenotyping using flow cytometry and fluorescence microscopy, 6 cytokine proliferation assay, 7 immunoglobulin gene rearrangement analysis, 8 cytogenetic preparation and analysis, 9,10 viral and mycoplasmal evaluation. 6,11 The immunomarkers employed are summarized in Table 1.…”
Section: Characterization Of Mutz-5 Cellsmentioning
confidence: 99%
“…[1][2][3] Immortal cell lines provide an inexhaustible source of homogeneous, defined malignant cells free from contamination with normal blood elements. Conversely, one of the most prominent disadvantages of using malignant cell lines as a model for primary malignancy is the possibility that the cells which become immortalized were selected for their ability to grow in vitro, and that the immortalized cell lines may not be truly representative of the primary malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, one of the most prominent disadvantages of using malignant cell lines as a model for primary malignancy is the possibility that the cells which become immortalized were selected for their ability to grow in vitro, and that the immortalized cell lines may not be truly representative of the primary malignancy. [1][2][3] Two of the genes commonly activated in patients with T cell acute lymphoblastic leukemia (T-ALL) or lymphoblastic lymphoma are SCL/tal (hereafter SCL) and LMO1. 4,5 It has recently been shown that SCL and LMO1 (or the closely related LMO2) proteins collaborate to induce T cell leukemia or lymphoma in transgenic mice.…”
Section: Introductionmentioning
confidence: 99%